2020
DOI: 10.1111/eea.13008
|View full text |Cite
|
Sign up to set email alerts
|

Pan trap color preference across Hymenoptera in a forest clearing

Abstract: Insect biodiversity reveals much about ecosystem health and function; however, field studies of insect community composition and diversity are often unintentionally biased by the sampling methods deployed in the study area. Pan traps, particularly yellow pan traps, are a common method for passive community assessment across a variety of taxonomic levels. Our study finds that the diversity, richness, and abundance of hymenopterans in pan trapping projects are significantly impacted by the color of the pan trap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Even if the potential bias was constant across all sites, by using pan traps to sample wild bees we may have under‐sampled certain taxa (Prendergast et al, 2020), in particular larger bees (Roulston et al, 2007). In addition, several studies assessed colour preference in Hymenoptera, showing that trap colour affects the diversity of sampled bees and that, in most cases, yellow pan traps collected the largest numbers of bees (Buffington et al, 2021; Krahner et al, 2021). To evaluate the completeness of our sampling effort, we estimated the rarefaction curves using a coverage‐based method (Chao et al, 2020) (Figure S2a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Even if the potential bias was constant across all sites, by using pan traps to sample wild bees we may have under‐sampled certain taxa (Prendergast et al, 2020), in particular larger bees (Roulston et al, 2007). In addition, several studies assessed colour preference in Hymenoptera, showing that trap colour affects the diversity of sampled bees and that, in most cases, yellow pan traps collected the largest numbers of bees (Buffington et al, 2021; Krahner et al, 2021). To evaluate the completeness of our sampling effort, we estimated the rarefaction curves using a coverage‐based method (Chao et al, 2020) (Figure S2a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Yellow pan traps are often utilised for monitoring the abundance and diversity of Hymenoptera, especially pollinators (Buffington et al, 2021; Campbell & Hanula, 2007; Wilson et al, 2008). Both Skvarla et al (2016) and Buffington et al (2021) found that yellow pan traps had a higher trap catch of sawflies in deciduous woodland than pan traps of other colours, which is consistent with other pan trap colour trials for sawflies in different habitats (Barker et al, 1997; Ritzau, 1988). Yellow pan traps have not been widely employed for trapping sawflies in spruce forests, and other trap designs such as malaise traps and yellow sticky boards are more commonly used (Holuša & Lubojacký, 2007, 2008), with yellow stickyboards being used to monitor P .…”
Section: Discussionmentioning
confidence: 99%
“…Despite trapping a relatively large number of sawfly species in this study (over 11% of the known UK species), the total number of sawfly adults captured was relatively low, which may have been due in part to the trapping method used. Yellow pan traps are often utilised for monitoring the abundance and diversity of Hymenoptera, especially pollinators (Buffington et al, 2021; Campbell & Hanula, 2007; Wilson et al, 2008). Both Skvarla et al (2016) and Buffington et al (2021) found that yellow pan traps had a higher trap catch of sawflies in deciduous woodland than pan traps of other colours, which is consistent with other pan trap colour trials for sawflies in different habitats (Barker et al, 1997; Ritzau, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Other flight interception traps, like window traps are also reliable methods to catch microhymenoptera. Colour pans are a more common way of collecting parasitoid wasps as well, although they need more attention and care when being deployed in the field and are more selective due to their attracting properties ( Buffington et al 2021 ). Light trapping is a rather unexplored method, but might also be useful to assess pteromalid diversity.…”
Section: Introductionmentioning
confidence: 99%